Asian Development Review. - Sawada, Yasuyuki (Asian development review, 2019)
It also discusses labor market returns to education and English language skills in the People Republic of China, agricultural and nonagricultural labor productivities in low and middle income economies in Asia, the Kuznets postulate on the association of structural transformation with increasing inequality for 32 developing and recently developed economies, the determinants of the nominal yields of Indian government bonds, and the effect of credit policy in the economy of the Republic of Korea.